Oral sildenafil versus bosentan for treatment of persistent pulmonary hypertension of the newborn: a randomized controlled trial - Aditya Kallimath; Sujata Deshpande; Pari Singh; Reema Garegrat; Satyan Lakshminrusimha; Rajesh Maheshwari; Pradeep Suryawanshi (BMC, 2024)
Abstract Background Access to inhaled nitric oxide (iNO) is limited in low resource settings due to non-availability and high cost. There is a need for research on low-cost alternative therapies for management of persistent pulmonary hypertension of the newborn (PPHN). We aimed to compare oral sildenafil and bosentan as monotherapy in the treatment of neonates with PPHN. Study design In this single-centre open-label randomized controlled trial (RCT), term and late preterm neonates with PPHN, defined as pulmonary arterial systolic pressure (PASP) > 35 mmHg and requiring fraction of inspired oxygen (FiO2) > 0.21, were randomized to receive oral sildenafil and bosentan. The primary outcome was reduction of PASP by 25% within 48 h after start of drug. Results Thirty-six neonates were analyzed (18 in each group). Initial PASPs were similar in both groups. The median (IQR) time for the primary outcome (PASP to reduce by 25% within 48 h) was 36 (24-48) h and 96 (48-120) h in sildenafil and bosentan groups respectively (p = 0.008). There was also a higher need to add other pulmonary vasodilators in bosentan group as compared to sildenafil group (p = 0.006). Conclusion Sildenafil was associated with quicker reduction of PASP and FiO2 in neonates with PPHN, as compared to bosentan. Large multicentre blinded trials to assess efficacy and safety of bosentan in comparison with other pulmonary vasodilators would help to get a clearer understanding of its role in the management of PPHN, particularly for use in resource-limited settings that lack iNO. Clinical trial registration: https://ctri.nic.in/Clinicaltrials/rmaindet.php? trialid=63997&EncHid=39716.16132&modid=1&compid=19[CTRI/2022/06/043328].